Multifunctional Application of Electrospun Fiber (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This Special Issue compiles collective contributions that comprehensively reflect the versatile applications and cutting-edge advancements of electrospun nanofibers across diverse fields. These include biomedicine and drug delivery, tissue engineering and regenerative medicine, environmental remediation and adsorption materials, air filtration and protective technologies, antibacterial and antifungal applications, and flexible electronics and energy devices. Each study offers a distinct perspective, which deepens the scientific and engineering insights into the design and fabrication of next-generation electrospun materials. It is anticipated that through the industry–academia–research collaborative model of "scientific breakthroughs led by universities and industrialization practices driven by enterprises", more electrospun nanofiber materials will transition from laboratory-scale research to real-world market applications. This will ultimately facilitate the full realization of the industrial value inherent in electrospun nanofibers.